2015
DOI: 10.1246/bcsj.20150373
|View full text |Cite
|
Sign up to set email alerts
|

Structural Design of Coordination Polymers Based on Manganese and Chromium Ions Bridged by Oxalate Ligands

Abstract: Coordination

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…complexes have been synthesized. 17–19 Meanwhile, in these compounds, the C–C bond between two carboxylate groups (–COO) promotes the formation of an extended π-system. Such an extended π-conjugated ligand may induce strong d–π hybridization in the framework and thus enhance the overall super-exchange interaction.…”
Section: Introductionmentioning
confidence: 99%
“…complexes have been synthesized. 17–19 Meanwhile, in these compounds, the C–C bond between two carboxylate groups (–COO) promotes the formation of an extended π-system. Such an extended π-conjugated ligand may induce strong d–π hybridization in the framework and thus enhance the overall super-exchange interaction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when trans-syn-trans -dicyclohexano[18]crown-6 exhibited a flat conformation, the cyclohexane incorporated into the crystal honeycomb holes prevented solvent incorporation. 24,25…”
Section: Introductionmentioning
confidence: 99%
“…In the course of study, we reported on several crystals of {[Mn II Cr III (oxalate) 3 ] – } with supramolecular cations. Although the {[Mn II Cr III (oxalate) 3 ] – } exhibited various dimensionalities in the crystals, such as 3D cage structures and typical 2D layers, these crystals tend to incorporate crystal solvent in the frameworks. The {[Mn II Cr III (oxalate) 3 ] – } networks have large pores – the size of a typical 2D honeycomb pore is 10–11 Å in diameter , .…”
Section: Introductionmentioning
confidence: 99%